A stochastic ground motion model for the urban environment. (January 2020) - Cacciola, P.; Tombari, A.
Abstract: Nowadays stochastic ground motion models used for the seismic analysis and design of structures take into account the soil deposit only, disregarding the presence of existing buildings nearby. However, it is well known that ground motion in urban environment is modified by the presence of buildings, mainly due to the radiation energy emitted from a vibrating structure in the soil that alters the seismic free field motion. This study is a first attempt to propose a stochastic ground motion analytical model able to take into account the influence of the urban environment. A simplified discrete model is developed so to consider the influence of the radiated wave field into the free field ground motion. Comparison in terms power spectral density functions and peak ground acceleration determined from the proposed ground motion model and those determined through conventional approaches are carried out. Numerical results clearly show the efficiency of the proposed model to capture this complex phenomenon in the stochastic seismic analysis of structures by improving the accuracy of the estimation of the peak response of above 30% . Limits of the proposed formulation are also discussed.